A systematic review of ECG findings in patients with COVID-19 (2020)
Introduction: Since the epidemic of COVID-19 attractedthe attention, reports were surrounding electrocardiographic changes in the infected individuals. We aimed at pinpointing different observed ECG findings and discussing their clinical significance. Methods: We conducted a systematic search in PubMed, Embase, and Scopus databases. We included eligible original papers, reports, letters to the editors, and case reports published from December 2019 to May 10, 2020. Results: The team identified 20 articles related to this topic. We divided them into articles discussing druginduced and non-drug-induced changes. Studies reported an increased risk of QTc interval prolongations influenced by different therapies based on chloroquine, hydroxychloroquine, and azithromycin. Although these medications increased risks of severe QTc prolongations, they induced no arrhythmia-related deaths. In the nondrug- induced group, ST-T abnormalities, notably ST elevation, accounted for the most observed ECG finding in the patients with COVID-19, but their relation with myocardial injuries was under dispute. Conclusion: This systematic review suggests that identifying ECG patterns that might be related to COVID-19 is vital. Provided that physicians do not recognize these patterns, they might erroneously risk the lives of their patients. Furthermore, important drug-induced ECG changes provide awareness to the health-care workers on the risks of possible therapies.